Perbandingan Kinerja Interlocking Stone Sebagai Penahan Tanah Dengan Perlindungan Vegetasi dan Non-Vegetasi Terhadap Laju Erosi - Prandono, Tri (CV. Green Publisher Indonesia, 2025)
Erosion is one of the major environmental issues causing land degradation, reduced soil productivity, and ecosystem damage due to sedimentation. Effective erosion mitigation requires appropriate technology, one of which is the application of retaining structures such as Interlocking stones. This study aims to compare the performance of Interlocking stones as a soil retaining structure with and without vegetation protection in reducing erosion rates. The research method employed a field experiment approach on sloping land with variations in slope gradient and types of productive vegetation cover. The results indicate that Interlocking stones combined with vegetation protection significantly reduces erosion rates compared to non-vegetated conditions. Vegetation contributes to soil stabilization by decreasing surface runoff and enhancing soil cohesion through root systems. In conclusion, the combination of Interlocking stones and productive vegetation is more effective and sustainable for erosion control compared to Interlocking stones without vegetation. Comparison of the two treatments shows that vegetation is able to significantly increase the effectiveness of Interlocking stones, namely the amount of runoff volume and the amount of sediment volume are smaller, namely producing 5.85 Lt/m² of runoff and 2.64 kg/m² of sediment. In the structure without vegetation shows a larger amount of runoff volume and the amount of sediment volume, namely the runoff volume of 10.97 Lt/m² and the sediment transported 4.75 kg/m² of runoff volume of 10.97 Lt/m² and the sediment transported 4.75 kg/m².